Aligning the principles of assessment for learning to learning in physical education: A review of literature. (4th July 2021) - Moura, André; Graça, Amândio; MacPhail, Ann; Batista, Paula
ABSTRACT: Background: A comprehensive international literature review on alternative assessment in physical education has been provided by López-Pastor et al. ([2013]. "Alternative Assessment in Physical Education: A Review of International Literature." Sport, Education & Society 18 (1): 57–76). The authors remarked that while more authentic forms of assessment in physical education have been evidenced over the last three decades, the extent to which alternative assessment practices have become common practice in the teaching of physical education is yet to be established. Purpose: This review provides an updated perspective on the prevalence of assessment for learning (AfL) principles in physical education discourse since the 2013 publication. The intent is to inform and consider future AfL practices in school physical education and physical education teacher education (PETE) programmes. Methods: Eligibility criteria for the review required full-text articles written in English or Spanish; published (open access and/or in print) in peer-reviewed, academic and professional journals; and limited to the period 2013–2019. Inclusion criteria required articles to report assessment being used to promote learning in physical education, regardless of making reference to 'assessment for learning'. Findings: Fifty-two articles met the inclusion criteria. A thematic analysis of these articles resulted in four themes: i) traditional positioning of assessment in physical education; ii) AfL and physical education; iii) the constraints in enacting AfL in physical education; and iv) how to most effectively embed AfL in daily physical education practices. Conclusions: The main conclusions of this review are that i) AfL is a learning-oriented assessment based on socio constructivist theories and integrated into the teaching-learning process, ii) physical education teachers continue to use assessment solely to grade students; iii) physical education teachers do not have the necessary skillset to use AfL in physical education successfully; iv) physical education teachers need to be supported to implement AfL; and v) it is necessary to consider how best PETE programmes can infuse AfL across the programme.